“QUO VADIS GOLD, AS SAFE HAVEN ASSET?” - Andersen, Christian; Suherman Sewu, Pan Lindawaty; Malinda, Maya; Lusiana, Floria; Salwa, Liana (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The development of Indonesian legal policies is very crucial for cryptocurrencies, it is very important to have national regulations that are able to answer the development of investments that are cross-border. This research proposal emphasizes that effective regulation of this new ecosystem requires the application of fundamental concepts and clear directions. There is skepticism from governments around the world including the Indonesian government over the clarity of the cryptocurrency market. On the other hand, digital currency is recognized by major industry players in the technology sector as a means of payment. A way is needed to protect the various parties involved in the cryptocurrency market. The problem that will be raised is how one of the crypto-currencies can be used as a safe haven to replace gold and how the law treats it, then look for the potential impact of crypto currency on the way of transactions and policies to monitor and control changes in the value of crypto currencies and is there a chance for a stable to be formed? new coin in Indonesia. The methodology used in this study is normative juridical, which uses secondary data, the primary legal material, namely various relevant laws and regulations, and the secondary legal material, namely books and legal literature. The methods (methods) used are statutory and conceptual. This study answers the research gap to find out the opportunities, risks, policy implications accompanied by qualified library sources, to know the challenges in enacting regulations, as well as safe criteria to ensure legal certainty, security and welfare of the Indonesian people, regulation and redefinition of virtual currencies and currencies. digital and its monitoring and regulatory factors to complement a predefined set of rules.